Phase Unwrapping InSAR Image Using Local Energy Minimization Approach - Adi, Kusworo; Mengko, Tati L.R.; Suksmono, Andriyan B.; Gunawan, Hendra (UI Scholars Hub, 2008)
Phase Unwrapping InSAR Image Using Local Energy Minimization Approach. Reconstruction process of phase data from its cover is called Phase Unwrapping (PU). Ideally, without any noise phrase, singularity, and aliasing problems, the phase information can be unwrapped easily. However, in fact, the phase data actually always get noise disturbance and discontinuity. The PU process becomes more complicated and needs a better PU algorithm to address the problems properly. In this research, the local PU algorithm is developed using minimization of close related firstorder pixels energy approach. In this method, the energy difference between four close related pixels is counted, followed by getting the probability value to obtain its total multiple ranges. Based on the research using synthesis ring image and InSAR with coherence 0.8, the Peak Signal to Noise Ratio (PNSR) range will be 30.5373 dB in 20 itteration.